Study of a bcc multi-principal element alloy: Tensile and simple shear properties and underlying deformation mechanisms. (1st January 2018) - Lilensten, L.; Couzinié, J.-P.; Perrière, L.; Hocini, A.; Keller, C.; Dirras, G.; Guillot, I.
Abstract: The impact of a concentrated solid solution on the deformation mechanisms of a bcc multi-principal elements alloy is investigated. The room temperature mechanical properties in tension and simple shear are studied on samples with controlled microstructure. The partition of the various stress components is performed, as well as the determination of the activation volumes and the analysis of the dislocation density and velocity. The study of the mechanical behavior is coupled to a complete TEM investigation. The alloy displays a high yield strength that is explained by a strong impact of the short-range obstacles to the dislocation glide, with an enhancement of the effective stress due to the concentrated solid solution. The increase of the backstress is related to the formation of a heterogeneous dislocation structure, with dense dislocation bands acting as long-range obstacles. Deformation is controlled by screw dislocation glide. The a/2<111> screw dislocations are rectilinear, indicating a high lattice friction effect. Evolution of both dislocation velocity and density during multirelaxation transients suggests a low mobility. If activation volumes are consistent with a Peierls mechanism, other considerations rather head towards the hypothesis of a transitory regime where the solid solution could impact further the dislocation glide. Graphical abstract: Image 1